Proposed Algorithm for Encrypting the(JPEG)Compressed Image (Al-Mansour Journal, 2022)
In image encryption algorithms, encryption security and encryption speed are important aspects in the field of data transmission (including digital image transmission) via the Internet, the need arises to protect data by encrypting it, in this paper proposes an algorithm that is characterized by precision and safety. It works in 15 rounds and applies encryption to the compressed image (JPEG), Taking into consideration data image of loss after the decryption process. The goal is to supply a highly secure encryption algorithm with increase the speed significantly based on field GF (P) that adopted in thealgorithm advance encryption standard (AES).
Keywords: cryptography; key generator; randomness; symmetric key; AES; block cipher; JPEG